Konsep Pendidikan Holistik Anak Usia 9-12 Tahun dalam Perspektif Islam: The Concept of Holistic Education for Children Aged 9-12 Years from an Islamic Perspective - Palah, Palah (Risalah Kharisma, 2023)
This study explores the concept of holistic education for children aged 9-12 years from an Islamic perspective, aiming to support their social-emotional, moral, and spiritual development. The main issue addressed is the lack of an integrated approach that combines Islamic values and modern educational methods to foster balanced growth. The purpose of this research is to examine how a holistic educational approach can nurture both cognitive and emotional-moral dimensions of children in this age group. The study uses a qualitative approach, reviewing existing literature and analyzing case studies emphasizing the importance of incorporating Islamic teachings into education. The findings show that a holistic approach, encompassing emotional intelligence, moral development, and spiritual growth, is essential in shaping well-rounded individuals. Furthermore, parental and school involvement, along with aligning Islamic values in the curriculum, are key to success. The study concludes that implementing a holistic education framework based on Islamic principles contributes significantly to children's character and well-being. Implications for educational practice include creating programs that balance cognitive, emotional, and spiritual learning for overall child development..